Smart Farm Control System Using IoT : https://doi.org/10.69692/SUJMRD0901373 - Orhpomma, Sounith; Soukhavong, Sengthong; Briatia, Xoxiong; Phomlasaboud, Khantavanh; Meanded, Siamphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This paper presents a way to do smart agriculture by using the advances in technology and information today, especially the Internet of Things (IoT) to help control the environment to change according to the needs of plants automatically. Which this research used the method of making a closed house or Greenhouse size 6m x 9m x 4m in number of 2 houses and using various types of sensor equipment. To detect parameters that affect the environment such as: Temperature sensor, Humidity sensor, Soil moisture sensor, pH sensor and Light sensor. To bring those values ​​forward to the microcontroller to process and order the electrical equipment to work, such as solenoid valves or water pumps; As well as send the parameter value to display the results to the application on the smartphone and the website through the wireless Internet system (WiFi) using the Blynk platform or Blynk cloud. From the results of the design and experiment, it was found that the system can control electrical equipment in the farm system, such as solenoid valves, water pump, and read various values ​​according to the set goals and objectives. We can order control Turn on and off the water system or the fog system anywhere at any time according to the conditions of the internet connection or direct control through the control box at any place or choose to have the system work automatically such as watering and misting according to the conditions we want and the system can also monitor or check the temperature, touch moisture, soil moisture, light intensity and pH value of the water at any time through the platform of the brand that can be used on both smartphones and computers.